GE_GERICHTE P/733/2018 vom 24. Januar 2019 - GE Cour de justice (2019)
VOL(DROIT PÉNAL) ; VIOLATION DE DOMICILE ; TENTATIVE(DROIT PÉNAL) ; ENTRÉE ILLÉGALE ; SÉJOUR ILLÉGAL ; EXPULSION(DROIT PÉNAL) ; ANTÉCÉDENT | CP.139.al1; CP.139.al2; CP.186; LEtr.115.al1.leta et b; CP.47; CP.49.al1; CP.42.al2; CP.66.ala.letc et d